MAKNA SIMBOLIK MAKNA SIMBOLIK TRADISI SEDEKAH BUMI DI DESA MEDANI KECAMATAN CLUWAK KABUPATEN PATI - Heri Heri; Situ Asih; Marjianto Marjianto (STABN Raden Wijaya Wonogiri, 2021)
Sedekah Bumi tradition is one of rituals traditional society in Java that has been going for generations from the ancestors’ Javanese people. The purpose of this study is to describe the process implementation of Sedekah Bumi Tradition, it carryout by society of Medani, Cluwak Pati. This research was a descriptive qualitative research. Data collection methods were through observation, interviews, and documentation, and the technique of validity the data through triangulation techniques. The location of this research is in Medani, Cluwak, Pati. This research was carried out from March to August 2021. Several processions are carried out in Sedekah Bumi Tradition (kabumi), namely Manganan, Kondangan, Mbangun tumbal, art and closings. The results of this study shows that the symbols that exist in Sedekah Bumi tradition as a tribute to the almighty. The symbolic meanings in Sedekah Bumi is interpreting human nature and teach virtue. The relevance of Sedekah Bumi tradition in Buddhism is existence of moral values as contained in the Buddhist’ Pancasila, harmony and love.